2020
DOI: 10.1016/j.exphem.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Iron in the Bone Marrow of a Murine Model of Hematopoietic Acute Radiation Syndrome

Abstract: Exposure to high-dose total body irradiation (TBI) can result in hematopoietic acute radiation syndrome (H-ARS), characterized by leukopenia, anemia, and coagulopathy. Death from H-ARS occurs from hematopoietic insufficiency and opportunistic infections. Following radiation exposure, red blood cells (RBCs) undergo hemolysis from radiation-induced hemoglobin denaturation, causing the release of iron. Free iron can have multiple detrimental biological effects, including suppression of hematopoiesis. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Collectively, these results showed that, although MDMs and MG are generally evenly distributed within untreated tumors, at recurrence, we observe the spatial emergence of localized clusters Although these analyses revealed different spatial patterns of TAMs in untreated versus RT-recurrent tumors, it did not enable the temporal discrimination of the sequence of cell infiltration throughout the experimental time course. Given that RT has been reported to lead to hemolysis and hemoglobin release in other contexts (46,47), we assessed whether this process is also evident in gliomas after RT and whether iron uptake by specific cells could thereby mark them in a temporal manner. We therefore stained PDG-Ink4a/Arf KO glioma sections with Prussian blue (PB) to visualize iron deposition.…”
Section: The Distribution Pattern Of Tams Within Tumors Changes After...mentioning
confidence: 99%
“…Collectively, these results showed that, although MDMs and MG are generally evenly distributed within untreated tumors, at recurrence, we observe the spatial emergence of localized clusters Although these analyses revealed different spatial patterns of TAMs in untreated versus RT-recurrent tumors, it did not enable the temporal discrimination of the sequence of cell infiltration throughout the experimental time course. Given that RT has been reported to lead to hemolysis and hemoglobin release in other contexts (46,47), we assessed whether this process is also evident in gliomas after RT and whether iron uptake by specific cells could thereby mark them in a temporal manner. We therefore stained PDG-Ink4a/Arf KO glioma sections with Prussian blue (PB) to visualize iron deposition.…”
Section: The Distribution Pattern Of Tams Within Tumors Changes After...mentioning
confidence: 99%
“…Our laboratory and others have demonstrated that radiation-induced hemolysis of RBC is associated with an accumulation of iron in the bone marrow in rodent models of H-ARS [ 27 , 28 ]. The reduction of circulating RBC increased iron in the plasma, and increased iron levels in hemosiderin in the bone marrow have been associated with increased levels of hepcidin expression in the liver following TBI [ 28 , 29 ]. This suggests that iron release from intestinal cells is suppressed in response to high plasma iron following TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory have shown that captopril mitigates ARS in mice and in Göttingen minipigs 27,46 . However, our current data indicate that captopril treatment did not mitigate radiationinduced reduction of RBC or HGB, or deposition of iron in the spleen.…”
Section: Discussionmentioning
confidence: 83%
“…Our laboratory and others have demonstrated that radiation-induced hemolysis of RBC is associated with an accumulation of iron in the bone marrow in rodent models of H-ARS 26,27 . Here we investigated the deposition of iron in the spleen following TBI in mice.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation